Ionization and ion transport : a primer for the study of gas discharges and plasmas - Go, David B. (IOP (Series). Release 22., 2022)
Gas discharges and non-equilibrium low-temperature plasmas form the basis for most plasma technologies. This book introduces engineering and science students to the basic underlying physics and chemistry concepts that form the foundation of plasma science and engineering.